Hydrogeochemical assessment of groundwater quality for drinking and irrigation in Biswanath and Sonitpur district of the Central Brahmaputra Plain, India - Goswami, Ritusmita; Neog, Nikita; Thakur, Ritu (Frontiers in Water, 2022)
In recent times, the contamination of groundwater in north-eastern states of India has become a reason for concern. The lack of appropriate irrigation water management hinders the practice of sustainable agriculture. Hence, it is vital to understand the groundwater quality for the proper planning and management of groundwater resources to ascertain its use for drinking and irrigation purposes. The current study was conducted in the districts of Biswanath Chariali and Sonitpur, Assam, India with an aim to evaluate the groundwater quality and its suitability for irrigation and drinking purpose. 56 water samples were collected from various sources across the two districts and analyzed for general physicochemical parameters and heavy metals namely arsenic (As) and iron (Fe). Groundwater suitability was evaluated by comparing the results of physicochemical analysis with Indian Standards and the results revealed the mean concentrations of the cations were observed in the order Na+>Ca2+>Mg2+>K+ whereas the anions in the order of HCO3->Cl->SO42->PO43-. Further, several parameters were considered for assessing the groundwater suitability for irrigation namely sodium adsorption ratio (SAR), sodium percentage (Na%), magnesium adsorption ratio (MAR), permeability index (PI), and Kelly’s index (KI). All parameters suggested the water to be suitable for irrigation except for MAR values which implied unsuitability. Moreover, high Fe and As were detected with 95% and 25% of the total respectively, exceeding the WHO permissible limit for drinking water. The highest concentration of As (0.08 mgL-1) was observed in Tewaripal, Biswanath Chariali, and Fe (32.20 mgL-1) in Gereki, Biswanath Chariali. Gibbs’s plot discerned the aquifers’ underlying hydrogeochemical processes such as silicate, carbonate, ion exchange, and reverse ion exchange processes predominated the region. A significant positive correlation was observed between As and PO4- which may indicate a common source of origin for both and maybe pinpoint the contribution of anthropogenic activities towards As enrichment. Overall, the study revealed that although the groundwater is apt for irrigation in regard to SAR, Na%, MAR, PI, and KI, however As and Fe concentrations suggest otherwise. The outcome of the study may be helpful to the farmers, and policymakers in planning and management of the groundwater resources.